Impact of accelerometer based in physical layer wireless networks - Mansor, Zuhanis; Khairulanwar bin Zulkafli, Muhammad (International Journal of Engineering and Technology, 2018)
The initial deployments of antenna in the handset consist of fixed non-rotated antenna for transmitting and receiving the signal in the wireless communication scenario. However, link correlation at the UE shows very bad performance when the handset rotates in landscape position. This paper evaluates the impact of accelerometer on the downlink propagation channel of 3G smartphone for non-line-of-sight links. The performance average received signal power is studied for user equipment. Results show that the exploitation of an accelerometer provide better performance in terms of received signal power when the handset rotated from portrait to landscape position. It can be concluded that the deployment of accelerometer can be used to improve existing 3G smartphone received signal. Results also indicate that accelerometer can be used to improve downlink throughput since the signal-to-noise-power is increased by approximately 16%.